Influence of Project Risk Management in Micro and Small-Scale Industries on Workers’ Occupational Health to Enhance Productivity: An Ergonomic Approach - Jagruti Dhande; Prasad Rane; Himanshu Dhande (International Journal of Industrial Engineering and Management)
In recent years, Micro and small-scale industries (MSSIs) have been facing significant challenges such as market competition, rapid technological advancements, evolving customer preferences, and resource constraints. To meet production goals with expensive machinery and limited skilled labor, MSSIs often run operations 24/7 with employees working in rotating shifts. Unfortunately, ergonomic concerns are commonly overlooked, leading to issues that impact worker absenteeism and productivity levels. A survey involving 47 MSSIs and 827 workers was conducted to assess the effects of shift work on health and sleep patterns. The questionnaires were designed and distributed among 1497 workers and 827 workers took part in this study and returned the questionnaire (response rate 55.24%). Statistically, the data was analyzed shift wise and Chi-square test was employed to find out whether the shift schedules were associated with various variables. Pearson correlation analysis was applied to explore the complex relationship between the variables and the correlation between each variable and absenteeism before and after the Ergonomic Training Program (ETP). This study reported that ETP helped to mitigate absenteeism by 3.23% and the labor productivity improved by 2.78% (2.875 labor/h). Workers get benefitted from improved health and well-being, reducing the physical and psychological burdens associated with shift work. Overall, both the industry and its employees gain from the application of ergonomic practices.